Synergistic Effects of Radiotherapy and Capsaicin on Colorectal Cancer (CaCo-2) and Normal Fibroblast (HDFn) Cell Lines In Vitro: Research | Open Access | 30 April 2026 - Hatif, Abbas; Abdul Rahman, Azhar; A. Abdulwahid, Talib; M. Ahmed, Naser (EDUCATUM Journal of Science, Mathematics and Technology, 2026)
Colorectal cancer is the second most frequent kind of cancer worldwide. The treatment may comprise surgery, chemotherapy, and radiation therapy. More than half of cancer treatments are derived from natural sources, such as capsaicin. The biggest challenge is to get the disease under control as much as possible while causing as little harm to the healthy tissues around it. Cells were treated with an extract, Capsaicin of (chili peppers) and irradiated at 1 Gy, 3 Gy and 5 Gy. The MTT test was used to determine viability, and absorbance was measured at 570 nm using a Counter reader (Mutiskan EX, Thermo Lab systems). Capsaicin extract has shown a potential radiosensitizing effect in vitro for colorectal cancer. The inhibition effect in the cell lines was not selective and is significantly different from conventional radiotherapy. Capsaicin extract from chili peppers concerted with radiation proved more effective in colorectal cancer cells than radiotherapy alone.